Vaccination Trends and Family-Level Characteristics Associated With Incomplete or Delayed Childhood Immunizations: The Healthy Start Study. Issue 4 (May 2023) - Zell-Baran, Lauren M; Starling, Anne P; Glueck, Deborah H; Bekelman, Traci A; Norris, Jill M; Adgate, John L; Brown, Jared M; Dabelea, Dana
Purpose: Assess family-level factors associated with childhood immunization schedule adherence. Design: Prospective cohort; Setting; The Healthy Start study enrolled 1, 410 pregnant women in Denver, Colorado 2009-2014 Subjects: Children with available vaccination data in medical records (0-6 years old) Measures: Vaccine schedule completion and compliance Analysis: Logistic regression comparing family-level factors that differ based on vaccine schedule adherence Results: Most immunizations required in Colorado for school entry were below national completion goals with 61.8% of participants (n = 532/861) completing the full vaccination series. Most participants received the first dose of individual vaccines on time (73.5% - 90.7%), but fewer received all doses on time (21.0% - 39.5%). Factors associated with not completing the vaccination series (OR [95% CI]) included: in-utero exposure to cigarette smoke (1.97 [1.41, 2.75]), single parent household (1.70 [1.21, 2.38]), children identified as non-White (Hispanic 1.40 [1.01, 1.94]; Black 1.88 [1.24, 2.85]; Other 2.17 [1.34, 3.49]), mothers not working outside the home (1.98 [1.46, 2.67]), and household income <70, 000 per year (<40, 000 1.93 [1.35, 2.75]; 40, 000-70, 000 1.64 [1.09, 2.46]). Conversely, families with more educated mothers (0.47 [0.29, 0.76]) and older parents (0.97 [0.94, 0.99]) were significantly more likely to complete the series. Conclusions: These findings may help identify groups at risk of immunization schedule non-adherence and may be used to target education/advocacy campaigns to reduce hesitancy and increase access in these populations.